Formulation and Evaluation of Gummy Candy from the Extract of Jathropa Leaf (Jatropha curcas L.) - Aulia, Gina; Sayyidah, Sayyidah; Fadhilah, Humaira; Ismaya, Nurwulan Adi; Indah, Fenita Purnama Sari (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
People are becoming more interested in nutraceutical preparations to maintain health as the world's health problems worsen. Jatropha curcas leaves (Jatropha curcas L.) have anthelmintic properties due to tannin compounds that act as anti-worms. This study aims to produce jelly candy preparations from Jatropha curcas leaves and evaluate these preparations. There are two stages of research: raw material preparation and verification, and jelly candy formulation. This study showed that the best concentration of Jatropha leaf extract was Formula 2. Based on the phytochemical test, there were alkaloids in the Jatropha leaf extract. The pH value of gummy candies preparations of castor leaf extract, weight uniformity test, passed the moisture content test because they met the requirements for a wide range of dosage values. Meanwhile, the Hedonic Test results show that Formula 2 is the most preferred by children. So, based on the evaluation and hedonic test results, Formula 2 is the best preparation for jelly candy from jatropha leaves.